2022
DOI: 10.1024/1662-9647/a000283
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Effects of Social Isolation During the COVID-19 Pandemic 2020

Abstract: Abstract. The SARS-CoV2 pandemic meant considerable restrictions in the social life of many people. Older people belong to the high-risk group for a severe to fatal course of the SARS-CoV2 disease, which is why these groups received special protection. This protection included drastic restrictions on their personal and social contacts, including the suspension of psychosocial therapies. This study examines the cognitive and emotional effects of social isolation on older people. A group of 49 participants who l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Most studies of the prevalence of depressive symptoms reported increased levels compared with pre-pandemic assessments (n = 12 studies) or community-dwelling older adults (n = 2 studies) while one of these studies reported conflicting results with no significant increase in depressive symptoms compared to the three proceeding years (McArthur et al 2021 ). Importantly, studies analyzing data collected at different times during the pandemic showed that depressive symptoms fluctuated with a high prevalence after the onset of social isolation and a subsequent decrease when visiting restrictions were relaxed (Angevaare et al 2022 ; Górski et al 2022a , b ; Górski, Garbicz, et al, 2022 ; Levere et al 2021 ; Plangger et al 2022 ). Interviews with residents conducted during later phases of the pandemic confirm little psychological impact at that time (Schweighart et al 2021 ; Thomas et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of the prevalence of depressive symptoms reported increased levels compared with pre-pandemic assessments (n = 12 studies) or community-dwelling older adults (n = 2 studies) while one of these studies reported conflicting results with no significant increase in depressive symptoms compared to the three proceeding years (McArthur et al 2021 ). Importantly, studies analyzing data collected at different times during the pandemic showed that depressive symptoms fluctuated with a high prevalence after the onset of social isolation and a subsequent decrease when visiting restrictions were relaxed (Angevaare et al 2022 ; Górski et al 2022a , b ; Górski, Garbicz, et al, 2022 ; Levere et al 2021 ; Plangger et al 2022 ). Interviews with residents conducted during later phases of the pandemic confirm little psychological impact at that time (Schweighart et al 2021 ; Thomas et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…In quantitative studies using interviews and surveys, concerns about accelerated cognitive decline were expressed by residents, proxies and HCP. Using longitudinal assessments one study reported a decline in MMSE scores between October 2019 and July 2020 (Greco et al 2021 ) and two others reported an increase in cognitive impairment from pre-isolation to post-isolation assessments (Górski et al 2022a , b ; Plangger et al 2022 ). Routine data from the Minimal Data Set showed a decline in cognitive function during the first months of the pandemic peaking in mid-April and then improving (Levere et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is a source of social interaction, cognitive stimulation, load sharing of emotional burden, and family bonding (Chen et al, 2020; Koenig et al, 2012) which may promote hope, optimism, and a sense of control (Krause & Hayward, 2016). Plangger et al (2022) have reported negative effects of pandemic-induced social isolation on cognitive function, anxiety, depression, and quality of life in older adults living in nursing homes. Supporting R/S practices during stressful times is therefore important, especially because older adults with ADRD are at greater risk of complications during a pandemic (Wang et al, 2021) and ADRD caregivers face greater physical, emotional, and financial burdens (Alzheimer’s Association, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The prevention of communicable diseases from being transmitted from a patient to other patients, health care workers and visitors, or from an outsider to a particular patient. Various forms of isolation exist, in some of which contact procedures are modified and others in which the patient is kept away from all other people (Plangger et al, 2022). When isolation is applied to a community or a geographic area, it is known as a cordon sanitaire.…”
Section: Literature Reviewmentioning
confidence: 99%